A dual-rotator fluorescent probe for analyzing the viscosity of mitochondria and blood. Issue 28 (10th March 2021) - Fu, Manlin; Sun, Yue; Kenry,; Zhang, Miao; Zhou, Haihua; Shen, Wei; Hu, Yi; Zhu, Qing
Abstract : A novel mitochondria-targeting molecular rotator FD was designed to visualize changes in viscosity under hypoxic conditions in vitro and in vivo . Abstract : A novel mitochondria-targeting molecular rotator FD was designed to visualize changes in viscosity under hypoxic conditions in vitro and in vivo . Importantly, FD can be used to detect changes in the blood viscosity of liver cancer and liver cirrhosis patients, and also rehabilitation of liver disease.